1996
DOI: 10.1038/bjc.1996.331
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of childhood cancer among siblings

Abstract: Summary The National Registry of Childhood Tumours contains over 51 000 records of children born in Great Britain who developed cancer under the age of 15 years. Patterns of childhood cancer among families containing more than one child with cancer have been studied. A total of 225 'sib pair' families have been ascertained from interviews with parents of affected children, from hospital and general practitioner records and from manual and computer searches of names and addresses of patients. A number of specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 20 publications
5
24
1
Order By: Relevance
“…The occurrence of childhood tumors among siblings to childhood cancer patients has previously been examined in four systematic population-based studies [4][5][6][7] and in two hospital-based series [8,9]. These studies showed similar results, with an overall two-fold increased risk for childhood and adolescent cancer in sibling.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The occurrence of childhood tumors among siblings to childhood cancer patients has previously been examined in four systematic population-based studies [4][5][6][7] and in two hospital-based series [8,9]. These studies showed similar results, with an overall two-fold increased risk for childhood and adolescent cancer in sibling.…”
Section: Discussionsupporting
confidence: 67%
“…The risk for childhood and adult tumors in first degree relatives to childhood cancer patients has previously been studied in several studies [4][5][6][7][8][9][10][11][12][13] Overall, most of the elevated risks could be attributed to known hereditary cancer syndromes. However, a small increased risk for childhood cancer in siblings remains even when families with known cancer predisposing disorders are excluded [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, two large studies from the United States and from England with exploration of 37 000 and 51 000 death certificates, respectively, indicated a twofold increased risk of leukemia among siblings to children with leukemia. 16,17 However, the studies did not distinguish between types of leukemia, and it is uncertain to what extent other severe bone marrow diseases or leukemoid reactions were misclassified as leukemias on the death certificates. More recently, a population-and register-based study from the Nordic countries revealed only two cases of non-twin leukemia (including one undifferentiated) among approximately 11 000 non-twin siblings to 6313 children with leukemia compared to the five cases that were expected by chance.…”
mentioning
confidence: 99%
“…Childhood brain cancer is encompassed in many rare cancer syndromes of high risk (Draper et al, 1996), but hereditary effects have been ascribed only to some 2-4% of brain cancers (Bondy et al, 1991;Hemminki et al, 2000c;Narod et al, 1991). In populationbased studies, the familial risk of brain tumours was 2.5, and in offspring of survivors of childhood brain tumours it was 2.0 (Sankila et al, 1998;Hemminki et al, 2000c).…”
Section: Parental Cancer As a Risk Factor For Nine Common Childhood Mmentioning
confidence: 99%